A reverse J-shaped association of leisure time physical activity with prognosis in patients with stable coronary heart disease: evidence from a large cohort with repeated measurements. Issue 13 (14th May 2014) - Mons, Ute; Hahmann, Harry; Brenner, Hermann
Abstract : Objective: To study the association of self-reported physical activity level with prognosis in a cohort of patients with coronary heart disease (CHD), with a special focus on the dose–response relationship with different levels of physical activity. Methods: Data were drawn from a prospective cohort of 1038 subjects with stable CHD in which frequency of strenuous leisure time physical activity was assessed repeatedly over 10 years of follow-up. Multiple Cox proportional hazards regression models were used to assess the association of physical activity level with different outcomes of prognosis (major cardiovascular events, cardiovascular mortality, all-cause mortality), with different sets of adjustments for potential confounders and taking into account time-dependence of frequency of physical activity. Results: A decline in engagement in physical activity over follow-up was observed. For all outcomes, the highest hazards were consistently found in the least active patient group, with a roughly twofold risk for major cardiovascular events and a roughly fourfold risk for both cardiovascular and all-cause mortality in comparison to the reference group of moderately frequent active patients. Furthermore, when taking time-dependence of physical activity into account, our data indicated reverse J-shaped associations of physical activity level with cardiovascular mortality, with the most frequently active patients also having increased hazards (2.36, 95% CI 1.05 to 5.34). Conclusions: This study substantiated previous findings on the increased risks for adverse outcomes in physically inactive CHD patients. In addition, we also found evidence of increased cardiovascular mortality in patients with daily strenuous physical activity, which warrants further investigation.